The effect of shear and bending capacities on impact behavior of RC beams - Wongmatar, P.; Hansapinyo, C.; Bi, K.; Vimonsatit, Vanissorn (2017)
The behavior of reinforced concrete beams under impact loading has been widely studied through experimental investigations. However, because of the limitation of the instruments, only the member behavior (e.g. the local behavior of reinforcement bars, stirrups and concrete) has been presented. With the use of 3D finite element modelling, more detailed information can be explored than with the experimental studies. This paper carries out numerical simulations on the impact behavior of Reinforced Concrete (RC) beams using an explicit finite element code LS-DYNA to investigate the local behaviors. First, the numerical models are validated by comparing the numerical results with the experimental values reported in the literature, in terms of impact force history, mid-span deflection history and damage patterns of RC beams. The simply supported RC beams with different bending capacities and shear capacities are analyzed under impact loading at mid-span. Moreover, the ultimate capacities under gradually increasing static point load at mid-span of the beams are also numerically investigated. Numerical results show that due to the effect of inertia force, transferred load at supports from the impact load at mid-span is smaller compared with that from static loading. It is found that the different shear-to-bending capacity ratio leads to different damage pattern and local behavior of the beams.